KINERJA PELAYANAN POLIKLINIK OBSTETRI DAN GINEKOLOGI DENGAN METODE PERFORMANCE PRISM DI RSIA SAMMARIE BASRA - Sormin, Kristee Grace; Oktamianti, Puput (UI Scholars Hub, 2022)
Analysis of unit service performance is very important for the improvement or growth of hospital services. This study discusses the analysis of the performance of the Obstetrics and Gynecology (Obgyn) Polyclinic service at SamMarie Basra Hospital using the Performance Prism method. This type of research is a qualitative study with the aim of getting a picture of stakeholder satisfaction, stakeholder contribution, strategy, process, and capability through in-depth interviews, observation and document review. The results of this study indicate that each stakeholder's satisfaction with the Obgyn Polyclinic's performance has not been maximized because most of the stakeholders' desires and needs have not been met. While the expected contribution of the hospital in terms of growth in visits and loyalty of Obgin patients has not been fulfilled. A number of existing Obgyn polyclinic strategies and those in the planning stage are still unable to improve service performance because the processes and implementation are not yet optimal as in the time management of officers and the process flow is not uniform. While in terms of capabilities, hospitals are still lacking in terms of the number of regulations / policies and human Resources. Overall performance analysis of Obgyn Polyclinic SamMarie Basra Hospital is still on the underperformance scale. It is necessary to improve service performance at the Obgyn Polyclinic so that it can improve service growth.